The Effect of Couched Peer Feedback through Face to Face and Facebook Interaction toward Students’ Writing Ability and Engagement - ANNISA ASTRID; LENNY MARZULINA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2018)
The purpose of this study was to find out how the implementation of couched peer feedback writing technique through direct interaction in the class and Facebook instruction influenced students’ writing ability and how they engaged in learning activities viewed from student’ level of writing anxiety. The research was conducted at two paragraph writing classes at one State Islamic University in Palembang. Mixed method data collection was used in this study. The quantitative data were collected by using Likert-scale questionnaire used to measure students’ level of writing anxiety and paragraph writing test. Meanwhile, the qualitative data were gained by using observation and interview. Students’ paragraph writing test scores were analyzed by using Two Way Anova statistical analysis. Then, observation and interview data were transcribed and coded. The findings showed that first, the difference feedback writing techniques had different effects on students' writing ability. Next, differences in students' anxiety levels in writing also had different effects on their writing performance. Then, there was no interaction between the application of feedback writing techniques, the level of writing anxiety and writing performance. Finally, students had varying engagement to the learning process in terms of behavioral, affective and cognitive aspects.